Interpretation of obstruction of justice in the crime of corruption in law number 31 year 1999 - Permai Yudi; Herry Anto Simanjuntak (Trigin Publisher, 2023)
If we look at Article 21 of Law No. 31/1999 on the Eradication of Corruption, there is no explicit definition of the act of